REHABILITASI DAN REVITALISASI EKS PROYEK PENGEMBANGAN LAHAN GAMBUT DI KALIMANTAN TENGAH - Ikhwanuddin Mawardi (Jurnal Teknologi Lingkungan, 2007)
One million hectare peat land development project in Central Kalimantan Province has been conducted based on Presidential Instruction, Number 80, 1998 dated June 5, 1995 for Foot Sustainability and followed by Presidential Degree, Number 82, 1995 dated for Development Of Peat Land To Be Utilized As Horticulture Field. The main goal of the project is to convert peat wet land into rice field, in the Central Kalimantan Province. This is also aimed to keep the rice self-support up attained by Indonesia in 1984. This program is in line with the government policy in fulfilling the foot supply, i.e. by extensification of newly open lands, increasing growing intensity to improve food productivity.